2019
DOI: 10.1080/19475705.2019.1609604
|View full text |Cite
|
Sign up to set email alerts
|

Annual precipitation and daily extreme precipitation distribution: possible trends from 1960 to 2010 in urban areas of China

Abstract: With global warming, precipitation events are often prone to intensify in some regions. Understanding the changing characteristics of annual and daily extreme precipitation as well as the underlying mechanisms plays an import role for early warning of precipitationinduced disaster (e.g. floods, landslides) and water resources management, especially in densely populated urban areas. In this study, we investigate the long-term trend of annual and daily extreme precipitation in China during 1960-2010 based on dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Climate change poses a huge challenge to water security in China, with extreme precipitation events becoming more frequent and intense (Xiao, 2017;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change poses a huge challenge to water security in China, with extreme precipitation events becoming more frequent and intense (Xiao, 2017;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although extreme precipitation involves the occurrence of high and low cumulative precipitation, the term extreme precipitation commonly refers in the literature to high cumulative rainfall in a shorter period of study. A set of 27 indices from the Climdex project (https://www.climdex.org, accessed on 20 March 2021) all derived from temperature and precipitation data have been widely used to investigate the frequency and trends of extreme precipitation at global (e.g., [4,5]), regional (e.g., [6][7][8]), and local (e.g., [9,10]) scales for historical and future periods under different scenarios. The results agree that there is medium confidence that anthropogenic influences have contributed to the intensification of extreme precipitation at the global scale [5,7,11], which is expected to continue under future projections [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in some urban agglomerations such as the Yangtze River Delta [47], Pearl River Delta [48,49] and Beijing-Tianjin-Hebei [50] have revealed that rapid urban expansion may cause significant increases in the amount of total precipitation in urban areas. Moreover, extreme precipitation may be intensified in the center of metropolitan areas [51], especially in the cities of Beijing, Guangzhou and Shanghai. In addition, precipitation intensity [52] and frequency [53] are more likely to increase in the metropolitan areas of these cities during the phase of rapid urbanization.…”
Section: Introductionmentioning
confidence: 99%